PENGARUH DOSIS KOMPOS AMPAS TEH DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI MENTIMUN (Cucumis sativus L.) - Della Amalia Febriani; Adriani Darmawati; Eny Fuskhah (BUANA SAINS, 2021)
Cucumber is a plant with many benefits and is liked by the community but has low productivity due to climate factors and farming techniques such as land management, fertilization, and irrigation. Increasing the productivity of cucumbers is carried out by utilizing the utilization of tea waste equipped with chicken manure to support plant growth. The aim of this research was to review the growth and production of cucumbers due to doses of compost tea and chicken manure. The research was carried out using a completely randomized design with a 4x4 factorial pattern with 3 replications. The first factor was the treatment of compost tea doses P0=control, P1=25 kg P2O5/ha, P2= 50 kg P2O5/ha, dan P3=75 kg P2O5/ha then the dose of chicken manure is A1= inorganic fertilizer, 150 kg P2O5/ha, A2= 75 kg P2O5/ha, A3=100 kg P2O5/ha, and A4=125 kg P2O5/ha The results showed that tea dregs compost and chicken manure have a significant effect on plant growth.The interaction between tea dregs compost and chicken manure gave a significant effect on the parameter of fruit weight with the best results at the treatment doses of 50 kg P2O5/ha /ha (P2) and 100 kg P2O5/ha /ha (A3).